ANALISIS NILAI TAMBAH DAN KEUNTUNGAN PT MITRA ALAS AGRI MINYAK SERAI WANGI DI DESA TERUSAN KECAMATAN BATURAJA TIMUR KABUPATEN OKU (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2021)
This study aims to analyze the added value and benefits of PT Mitra Alas Agri Serai Wangi Oil in the village of Terusan, Baturaja Timur District, OKU Regency, which has been carried out from April to June 2021. This research was carried out at PT Mitra Alas Agri Oil of Serai Wangi in the village of Terusan. East Baturaja District, OKU Regency. The method used in this research is a survey method. The conclusion obtained in this study is that the business of processing citronella into essential oil at PT Mitra Alas Agri Serai Wangi Oil produces added value in one kilogram of citronella raw materials of Rp. 469.289 /kg means that for every one kilogram of raw materials used citronella gives an additional value of Rp. 469,289 in the production of citronella essential oil with a value added ratio of 41.927% in 2019 while in 2020 the added value generated was Rp. 469.389 /kg with a value added ratio of 41.895%. The profits obtained are 5.123% and 10.473%, respectively. Keyword: value added , profit, lemongrass oil